Exploration and Analysis of Educational History from the Perspective of Educational Environmental History and Environmental History. (3rd August 2022) - Li, Wei; Li, Li
Abstract : The emergence of environmental historiography, for the first time, organically combined the history of the environment and human history and began to pay attention to the close relationship between human social changes and environmental changes. This paper explores the impact of environmental history on education from the perspective of environmental history. This paper explores and analyzes the history of the educational environment from the perspective of environmental history and studies the laws and characteristics behind the evolution of the relationship between education and environment. This paper analyzes the influence of environmental history on the three views of college students under environmental education. Further analysis of educational environmental history is improved to improve the three views of college students and promote the social development of research significance. The study of educational environmental history is of great significance to enlarge the field of educational history research, enrich the content of educational history research, and perfect the discipline construction of educational history. At the same time, the environmental perspective and ecological consciousness of educational environmental history research are the embodiment and adherence of Marxist historical materialism and environmental view.